Pore Nucleation Mechanism of Self-Ordered Alumina with Large Period in Stable Anodization in Citric Acid. Issue 9 (1st June 2018) - Ma, Yingjun; Wen, Yihao; Li, Juan; Lu, Jiangbo; Li, Yuxin; Yang, Yuanxun; Feng, Chenchen; Hao, Changchun; Zhang, Zhiying; Hu, Jing; Sun, Runguang
Abstract : We have demonstrated that self-ordered porous alumina with large period can be obtained by stable anodization in citric acid at high voltage (400 V). Pore nucleation, which determines the final morphology of the alumina, is a very slow process. By comparing the alumina films obtained in different citric acid concentrations and temperatures, we found the amount of free citric acid anions is critical to pore nucleation. Surface chemistry and the detail structural composition of the porous alumina were investigated by XPS and TEM, respectively. The results show that uniform black alumina surface (forming ordered nanopores) cannot be obtained in low or high citric acid concentrations; the carbon element content of the black is obviously higher than that of gray surface (pores cannot well develop); citric acid is incorporated into the porous alumina cell, where the thickness ratio of compact skeleton and acid incorporated part is 1:3. Accordingly, the pore nucleation has two stages: I, fast forming flat barrier-type alumina film, alumina form and deposit at metal-oxide and oxide-electrolyte interface, respectively. II, Al-citric complex in electrolyte slowly transform to citric acid incorporated alumina and unevenly deposit on barrier-type alumina, which results in electric field concentration between protuberances and pore development.